Sleep Quality is Associated with Total Cholesterol of Geriatric Patients in RSUD Dr Moewardi - Mastura, Rila Ruis; Budiningsih, Fatichati .; ., Suyatmi . (Nexus Kedokteran Klinik, 2016)
Introduction: Hypercholesterolemia refers to condition where levels of cholesterol in theblood are higher than normal reference. In Indonesia, prevalence of hypercholesterolemia are continously increased. Growing evidences indicate there is a relationship between sleep and hypercholesterolemia. The aim of this study was to examine relationship between sleep quality and total cholesterol of geriatric patient. Methods:This study usedobservational analytic method with cross sectional approach. Geriatric patients (n=30) in Geriatric Polyclinic RSUD Dr. Moewardi were recruited in this study used convenience sampling based on inclusion and exclusion criteria.Variables in this study were sleep quality, body mass index (BMI) and total cholesterol. Sleep quality was measure during face to face interviews using validated Pittsburgh Sleep Quality Index Indonesian translation. Total cholesterol was gotten from laboratory test result which was performed a day before. BMI was calculated from direct measurement of weight and height. Data were analyzed by Chi-Square test. BMI as confounding factor was assessed by Mantel-Haenszel. Results:There was a statistically significant positive association between poor sleep quality and total cholesterol of geriatric patients(p=0.029 significance level Î± = 0.05). Compared with good sleepers, relative risk (odds ratio) of having cholesterol > 200 mg/dl among poor sleepers was 5.78(95% CI,1.12-29, 85). Conclusions: This study found Â association between sleep quality and total cholesterol of geriatric patients in RSUD Dr. Moewardi. Keywords: Total cholesterol, sleep qualityÂ